Geological contacts - central Northern Calcareous Alps (Eastern Alps, Austria) - Oscar Fernandez (PANGAEA, 2025)
Geological mapping in the central Northern Calcareous Alps (Eastern Alps, Austria) during the years 2021 to 2023 has been performed. The aim of mapping has been to revise the 1:50,000 scale geological maps published by the Austrian Geological Survey (GBA/Geosphere) for inconsistencies in lithostratigraphic identification and contact definition. Critically, maps in the area were completed at a time when the emplacement of thrust sheets through gliding tectonics was still the dominant paradigm and pre-date advances in salt tectonics (see Fernandez et al., 2024, for a complete discussion). In consequence, mapping has aimed to correctly identify contacts compatible with salt tectonics, units remobilized in mass-transport deposits, low-angle thrusting, and syn-orogenic extension. The focus has been on two key areas of the central Northern Calcareous Alps: the Traun River and the Lammertal River valleys (roughly between longitudes 13° and 14°E, latitudes 47°30 extquotesingle and 48°N). Revised geological contacts (stratigraphic contacts and faults) are provided as SHP files. Stratigraphic contacts contain attributes describing the stratigraphic unit above and below and the type of contact. Faults contain information relating to type and sense of throw. No polygons have been generated. Data are in WGS84 UTM33 coordinates.